Anaemia of inflammation in sickle cell disease: A review of aetiopathogenesis, management, and prevention of sterile and septic inflammation in patients with sickle cell disease - Ahmed SG; Ibrahim UA (Ibom Medical Journal)
Background: SCD is strongly associated with sterile inflammation (STERIN) and septic inflammation (SEPTIN). Thus, in addition to haemolysis, anaemia in SCD has dual ‘inflammatory’ components; (1)-anaemia of sterile inflammation (ASTERIN) and (2)-anaemia of septic inflammation (ASEPTIN). Hence, the need to explore the relatively understated but important concept of ‘anaemia of inflammation in SCD’.